Assessing Parent-Adolescent Substance Use Discussions Using the Continuous Assessment of Interpersonal Dynamics. Issue 6 (24th October 2022) - Meisel, Samuel N.; Colder, Craig R.; Hopwood, Christopher J.
Abstract: Assessing parent-child interactions is critical for understanding family dynamics, however tools available for capturing these dynamics are limited. The current study sought to examine the validity of the Continuous Assessment of Interpersonal Dynamics (CAID) for understanding the dynamics of parent-adolescent substance use discussions. Specifically, we examined how CAID parameters were related to indicators of parenting and substance use. Sixty-one parent-adolescent dyads ( M adolescent age = 14.02, 57% female; M parent age = 46.40; 98% female) completed three 9-minute video-taped conflict, alcohol, and cannabis discussions as well as self-report measures of parenting (e.g., monitoring, psychological control) and substance use behaviors (e.g., intentions, use with parental permission). Interactions were coded using the CAID which provides continuous assessments of parent and adolescent warmth and dominance. Parental warmth, adolescent warmth, and dominance complementarity CAID parameters were positively associated with adaptive parenting and negatively associated with maladaptive parenting factors. Parental warmth in the cannabis discussion was negatively associated with the substance use and intentions factor. These findings support CAID as a reliable and valid assessment of interpersonal dynamics that characterize parent-adolescent substance use discussions and suggest that substance use conversations may be most effective when parents and adolescents act warmly throughout the discussion and exhibit dominance complementarity.